MiR‐483 inhibits bovine myoblast cell proliferation and differentiation via IGF1/PI3K/AKT signal pathway. Issue 6 (13th November 2018) - Song, Chengchuang; Yang, Zhaoxin; Dong, Dong; Xu, Jiawei; Wang, Jian; Li, Hui; Huang, Yongzhen; Lan, Xianyong; Lei, Chuzhao; Ma, Yun; Chen, Hong
Abstract: MicroRNAs (miRNAs) have been established to regulate skeletal muscle development in mammals. However, few studies have been conducted on the regulation of proliferation and differentiation of bovine myoblast cells by miRNAs. The aim of our study was to explore the function of miR‐483 in cell proliferation and differentiation of bovine myoblast. Here, we found that miR‐483 declined in both proliferation and differentiation stages of bovine myoblast cells. During the proliferation phase, the overexpression of miR‐483 downregulated the cell cycle–associated genes cyclin‐dependent kinase 2 ( CDK2 ), proliferating cell nuclear antigen ( PCNA ) messenger RNA (mRNA), and the protein levels. At the cellular level, cell cycle, cell counting kit‐8, and 5‐ethynyl‐2´‐deoxyuridine results indicated that the overexpression of miR‐483 block cell proliferation. During differentiation, the overexpression of miR‐483 led to a decrease in the levels of the myogenic marker genes MyoD1 and MyoG mRNA and protein. Furthermore, the immunofluorescence analysis results showed that the number of MyHC‐positive myotubes was reduced. In contrast, the opposite experimental results were obtained concerning both proliferation and differentiation after the inhibition of miR‐483. Mechanistically, we demonstrated that miR‐483 target insulin‐like growth factor 1 ( IGF1 ) and downregulated the expression of key proteins in the PI3K / AKT signaling pathway. Altogether, our findings indicate that miR‐483 acts as a negative regulator of bovine myoblast cell proliferation and differentiation. Abstract : MicroRNA‐483 (miR‐483) inhibits bovine myoblast cell proliferation and differentiation by targeting insulin‐like growth factor 1 (IGF1) and downregulated the expression of key proteins in the PI3K/AKT signaling pathway. These results will provide an insight target in breeding strategies appealing to cattle industry.